Development of a monitoring book for maternal dental health to prevent the risk of stunting - Junaidi, Junaidi; Asio, Asio; Muliadi, Muliadi; Keumala, Cut Ratna; Nurdin, Nurdin (Riset Informasi Kesehatan, 2024)
Background: Stunting has serious impacts, including impaired brain development leading to reduced intelligence, increased risk of disease, and higher risk of mortality. Stunting can occur during pregnancy due to inadequate nutritional intake, improper dietary patterns, and low-quality food, all of which hinder a child's growth. Efforts to prevent stunting have been implemented since pregnancy, especially during the first 1,000 days of life (HPK). Method: This research uses the Research and Development (R&D) method according to Borg and Gall (2003) with the following stages: 1) Identifying potential problems, 2) Data collection, 3) Product design planning, 4) Product creation, 5) Development: Internal testing. Internal testing involves expert validation to assess the feasibility of the product before it is used by the public, as well as user validation to ensure it is suitable for effectiveness testing in further research. Results: This study shows that the "Monitoring Book for Maternal Dental Health to Prevent the Risk of Stunting" has a very high feasibility level based on expert validation (96%) and respondent validation (86%). Conclusion: The book is considered effective and easy to understand by users. It is highly needed among the community and healthcare workers to raise awareness among pregnant women about the importance of maintaining oral and dental health to prevent the risk of stunting. The book is also considered practical for use as educational material at home.